2016
DOI: 10.2967/jnumed.115.166348
|View full text |Cite
|
Sign up to set email alerts
|

Serial 18F-FDG PET for Monitoring Treatment Response After Allogeneic Stem Cell Transplantation for Myelofibrosis

Abstract: Our objective was to assess the feasibility of 18 F-FDG PET/CT for noninvasive monitoring of treatment response after allogeneic stem cell transplantation (SCT) for myelofibrosis. Methods: Twelve patients with myelofibrosis underwent 18 F-FDG PET/CT before and after SCT. Bone marrow uptake, spleen uptake, and spleen size were assessed before and after SCT and compared with hematologic response criteria and bone marrow biopsies. Results: All patients who did not achieve complete remission remained PET-positive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
(13 reference statements)
0
7
0
Order By: Relevance
“…The review summarized that inflammation and colony-stimulating factors caused a diffuse FDG uptake in the bone marrow that was higher than the physiological FDG uptake in the liver. Diffuse FDG uptake in the BM has also been found in myeloproliferative neoplasms [11,12], while hyperplastic hematopoietic islands in aplastic anemia showed island-like and localized FDG uptake [13,25], and BM reconversion with island-like and localized FDG accumulation following the treatment of malignant tumors were observed. Although multiple myeloma had a relatively low diffuse uptake in BM, the CT often showed bone abnormalities such as osteolytic mass and fracture [24].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…The review summarized that inflammation and colony-stimulating factors caused a diffuse FDG uptake in the bone marrow that was higher than the physiological FDG uptake in the liver. Diffuse FDG uptake in the BM has also been found in myeloproliferative neoplasms [11,12], while hyperplastic hematopoietic islands in aplastic anemia showed island-like and localized FDG uptake [13,25], and BM reconversion with island-like and localized FDG accumulation following the treatment of malignant tumors were observed. Although multiple myeloma had a relatively low diffuse uptake in BM, the CT often showed bone abnormalities such as osteolytic mass and fracture [24].…”
Section: Discussionmentioning
confidence: 92%
“…FDG-PET/CT has enabled less invasive visualization of glucose metabolism in BM throughout the body, which was considerably difficult with conventional morphological imaging such as CT and magnetic resonance imaging [10]. Recently, FDG PET/CT has been increasingly applied to the diagnosis of bone marrow failure such as myeloproliferative neoplasm, aplastic anemia, and myelodysplastic syndrome as well as malignant lymphoma and multiple myeloma [11][12][13][14]. Some studies have reported that the region-of-interest was manually placed on certain bones and based on the semi-automatic measurement method for quantitative evaluation of BM [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…One pilot study retrospectively evaluated 12 MF patients in whom 18 F-FDG PET scans and BM biopsies were available both before and after allo-SCT (range: 100–442 days). A decrease in SUVmax_bm post-transplantation was found to correspond to a decrease in fibrosis grade [ 74 ]. Using the IWG-MRT criteria as the reference standard, the sensitivity of 18 F-FDG PET for detecting residual disease was 100%, with a specificity of 83% and negative and positive predictive values of 100 and 86%, respectively [ 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…A decrease in SUVmax_bm post-transplantation was found to correspond to a decrease in fibrosis grade [ 74 ]. Using the IWG-MRT criteria as the reference standard, the sensitivity of 18 F-FDG PET for detecting residual disease was 100%, with a specificity of 83% and negative and positive predictive values of 100 and 86%, respectively [ 74 ]. Risk of bias seems low, although the initial indication for imaging and patient inclusion criteria were unclear, and uncertainty regarding the blinded interpretation of the reference test exists (Table 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to distinguish between an inflammatory response and the stimulation of certain types of malignancy, recent chemotherapy, or administration of hematopoietic growth factors. 20 Although FAP is mainly expressed in lesions characterized by activated interstitial tissue, 11 68 Ga-FAPI PET/CT can distinguish between inflammatory and fibrotic activities in some diseases, such as IgG4-related disease and AS-related disease. 21 The present study also found that 68 Ga-FAPI did not show a significant uptake in the bone marrow of patients with MF in the early stages of obvious inflammation, whereas 68 Ga-FAPI uptake increased with an increase in the histopathological grade of MF in the middle and late stages.…”
Section: Discussionmentioning
confidence: 99%